Quantitative analysis of morphometric traits affecting yield performance in diverse soybean lines (Glycine max L. Merr) - Anna Satyana Karyawati; Aula Larasati; Sarah Ghina; Soni Sumarsono; Vina Mafazatul Ula (Cogent Food & Agriculture)
Developing superior soybean lines with high productivity requires thorough identification of morphological diversity to select desirable agronomic traits. This study focuses on the morphometric analysis of various soybean lines (Glycine max L. Merrill) to support the development of high-yield varieties. Conducted at the BSIP AKABI Kendalpayak Malang Experimental Farm, the study employed a randomised complete block design with 30 selected lines and six parent varieties. Key yield-related traits including pod length, pod width, and seed thickness were analysed. Results showed substantial variability; for example lines UBASK41 and UBASK22 exhibited median pod lengths of approximately 9.2 cm, which correlates positively with yield potential, whereas UBASK14 and UBASK33 had shorter pod lengths around 6.5 cm. Seed width and thickness also varied, with UBASK64 reaching a maximum pod width of 22 mm, and UBASK32 showing greater seed thickness, indicating these lines’ potential for larger, high-quality seeds. Path analysis and PCA revealed strong associations between specific morphometric traits and yield-related outcomes. These findings underscore the utility of morphometric analysis in selecting soybean lines with superior agronomic traits, thus supporting breeding programs aimed at yield optimisation.